Composite powders with carbon nanotubes for laser printing of electronics. (September 2022) - Słoma, Marcin; Wierzbicki, Michał; Skalski, Andrzej
Abstract: The purpose of this work is to develop electrically conductive composite fine powder containing carbon nanotubes, for use in the laser printing technique. This requires the evaluation of several approaches to the mixing of thermofusible powder with carbon nanotubes. For the experiments, a commercial toner for HP laser printer was used as a matrix and multiwalled carbon nanotubes as a conductive phase. Due to the fine powder morphology, carbon nanotubes should also be compatible with the laser printing technique. Several approaches were evaluated for obtaining a fine composite powder with carbon nanotubes, including ultrasonic stirring and low energy ball milling process. The obtained fine powder was tested towards compatibility with a desktop laser printer. Due to the complexity of the laser printing process, we decided to use the thermal transfer method, one of the elements of the laser printing technique. Adhesive properties evaluations and electrical measurements of powders with various amounts of nanotubes (10–30 wt%) were examined. This allowed selecting the composition of 18–20 wt% of carbon nanotubes as optimal, exhibiting proper adhesion to the paper substrate and with resistance in the range of 10 2 Ω. For the samples with appropriate adhesion to the substrate, we observe a trend of increasing conductivity with increased nanotube content. The developed composite is compatible with the laser printing technique, but it requires higher pressure than applied by commercial laser printers during the process of melting into the paper substrate. Highlights: Laser printing technique is not extensively investigated for printed electronics. Carbon nanotube fine powder should be compatible with laser printing technique. Properties of carbon nanotubes allow obtaining conductive paths on paper substrate. Mixing technique and solvent influence properties of final printed conductive paths. Conductive toner requires higher pressure than applied by commercial laser printers.